Toward rational management of patent ductus arteriosus: ductal disease staging and first line paracetamol. (2nd December 2021) - Sehgal, Arvind; Nitzan, Itamar; Krishnamurthy, Mohan B.; Pharande, Pramod; Tan, Kenneth
Abstract: Aims: To study paracetamol (PCM) use as first line therapy for significant patent ductus arteriosus (sPDA) closure, stratified by echocardiography. Methods: In this retrospective observational study, a prepublished score comprising PDA size and velocity, PDA:left pulmonary artery ratio, diastolic flow in main and LPA, LA:Ao ratio and left ventricular:aortic ratio were included for shunt severity. Successful closure was defined a priori as closure or ≥50% reduction in score. Comparisons were made between infants with sPDA who were treated and not treated. Results: During November 2017–2018, 227 infants from 23 to 31 +6 weeks' gestational age (GA) were admitted; 50 (22%) infants were diagnosed with PDA, 32 treated with PCM, overall treatment rate of 32/227 (14%). Successful therapy was noted in 23/32 (72%) and was higher when treated at ≤7 days (80 versus 68%, p  = .68), in infants >26 weeks GA (62.5 versus 100%, p  = .07) and BW >1000 g (65.4 versus 100%, p  = .14). Univariate analysis noted statistical significance only for GA. Eighteen infants were managed conservatively. Treated infants had a lower GA and BW, higher composite ECHO score (14.4 ± 0.5 versus 19 ± 0.4, p  < .001). Conclusions: Composite scoring helped reduce exposure, and focus more on infants with lower GA and BW with greater shunt severity.